(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This study aimed to examine the analytical thinking skills development through learning management plans. Research and development design coupled with case study method was employed to Thai Basic Education University students from a public university in Khon Kaen province, Thailand. There were two groups of samples consisted of 45 teacher educators and 1,575 Basic Education university students. The quantitative finding indicated that teacher educators’ analytical thinking score was 36.54 out of the full score as 45, higher than defined criterion of 70 percent while focus group interviews showed positive feedback including analytical thinking knowledge and practices in handling learning management.